2008
DOI: 10.1111/j.1365-3121.2008.00834.x
|View full text |Cite
|
Sign up to set email alerts
|

Mesozoic transpression, transtension, subduction and metallogenesis in northern and central California

Abstract: Middle Paleozoic to Middle Jurassic terrane assemblies in the Klamaths and Sierran Foothills consist of mafic-ultramafic complexes + fine-grained terrigenous strata derived from previously accreted continental-margin belts. Sutured oceanic terranes reflect c. 230 Myr of margin-parallel slip involving chiefly transtension and transpression. Quartzofeldspathic clastic rocks and blueschists ± eclogites are very rare. Little devolatilization occurred at magmagenic depths; hence, coeval hydrothermal ore deposits an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 129 publications
0
12
1
Order By: Relevance
“…During the Jurassic and Early Cretaceous, when many of the Franciscan eclogites were formed and exhumed, subduction is thought to have been oblique (Wakabayashi, 1992). However, it has also been suggested that effusive continental arc magmatism during the mid-Cretaceous required more normal convergence (Ernst et al, 2008).…”
Section: Ascent Rates In Serpentinite Channels and The Role Of Obliqumentioning
confidence: 99%
“…During the Jurassic and Early Cretaceous, when many of the Franciscan eclogites were formed and exhumed, subduction is thought to have been oblique (Wakabayashi, 1992). However, it has also been suggested that effusive continental arc magmatism during the mid-Cretaceous required more normal convergence (Ernst et al, 2008).…”
Section: Ascent Rates In Serpentinite Channels and The Role Of Obliqumentioning
confidence: 99%
“…Through Middle Jurassic time, largely oceanic terranes that formed seaward and ultimately were assembled in the Klamaths and the Sierran Foothills, consist chiefly of intensely imbricated mafic-ultramafic complexes and superjacent, fine-grained terrigenous strata derived from previously accreted continental margin belts [e.g., Burchfiel and Davis, 1981;Wright, 1982;Dickinson, 2008;Ingersoll, 2008]. Although commonly regarded as products of convergent plate tectonic processes, sutured ophiolite + chertargillite terranes apparently reflect $230 Myr of dominantly margin-parallel slip, involving minor stages of transtension and transpression [Saleeby, 1981[Saleeby, , 1982[Saleeby, , 1983Silberling et al, 1987;Irwin, 2003;Ernst et al, 2008]. Felsic igneous units, quartzofeldspathic clastic rocks, and high-pressure metamorphic lithologies occur but are uncommon.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Conducting new mapping and petrotectonic studies in medial belts of the Klamath Mountains and the southern Sierran Foothills, and building on the contributions of many earlier workers, Ernst et al [2008] proposed a plate tectonic scenario that described important aspects of the mid-Paleozoic -Mesozoic crustal growth of northern California. Through Middle Jurassic time, largely oceanic terranes that formed seaward and ultimately were assembled in the Klamaths and the Sierran Foothills, consist chiefly of intensely imbricated mafic-ultramafic complexes and superjacent, fine-grained terrigenous strata derived from previously accreted continental margin belts [e.g., Burchfiel and Davis, 1981;Wright, 1982;Dickinson, 2008;Ingersoll, 2008].…”
Section: Introductionmentioning
confidence: 99%
“…Middle Paleozoic to Middle Jurassic sequential terrane dockings in the Klamath Mountains and the Sierra Nevada Foothills produced an amalgam consisting chiefly of mafic–ultramafic oceanic complexes, each overlain by fine‐grained terrigenous strata derived from previously accreted continental‐margin belts (Irwin 1981; Ernst et al. 2008).…”
Section: Plate‐tectonic Sketches Of Study Areasmentioning
confidence: 99%
“…Middle Paleozoic to Middle Jurassic sequential terrane dockings in the Klamath Mountains and the Sierra Nevada Foothills produced an amalgam consisting chiefly of mafic-ultramafic oceanic complexes, each overlain by fine-grained terrigenous strata derived from previously accreted continental-margin belts (Irwin 1981;Ernst et al 2008). In the Klamaths, from east to west, these include the Eastern Klamath terrane, the Central Metamorphic Belt, the Western Paleozoic and Triassic Belt, and the Western Klamath terrane.…”
Section: Northern California Marginmentioning
confidence: 99%